2013
DOI: 10.1590/s1984-29612013000200046
|View full text |Cite
|
Sign up to set email alerts
|

Calodium hepaticum (Nematoda: Capillariidae) in synanthropic rodents (Rattus norvegicus and Rattus rattus) in Eastern Amazonia

Abstract: Calodium hepaticum (syn. Capillaria hepatica) is a trichurid nematode that parasitizes the hepatic parenchyma of rodents and other mammals. Infections in humans are rare, although they have been reported worldwide. A number of factors contribute to the distribution of this zoonosis, particularly the presence of dense populations of rodents associated with relatively poor urban environments, such as those found in parts of the northern Brazilian city of Belém in the eastern Amazon Basin. This study quantified C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
1
14
0
2
Order By: Relevance
“…The prevalence in this study is high and similar to that found in the states of São Paulo (59%) 5 , Bahia (56%) 8 and Pará (42%) 13 . The short life cycle of rats causes rapid release of large numbers of eggs in the environment.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…The prevalence in this study is high and similar to that found in the states of São Paulo (59%) 5 , Bahia (56%) 8 and Pará (42%) 13 . The short life cycle of rats causes rapid release of large numbers of eggs in the environment.…”
supporting
confidence: 87%
“…In Brazil, this parasite has been reported infecting humans and various species of domestic and wild mammals 2,12,13,14,15,18,20 . In synanthropic rodents, C. hepaticum has been recorded in the states of São Paulo, Bahia and Pará 5,7,13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Records of the nematode were also recently registered in the city of Belém, in Eastern Amazon (Moreira et al, 2013). In most rodents, infection by C. hepaticum ranges from mild to severe, but it is not associated with a clinical disease.…”
Section: Discussionmentioning
confidence: 99%
“…The same fact might explain the prevalence of A. cuniculi in Tenerife and El Hierro. Finally, C. hepaticum is a cosmopolitan zoonotic nematode that parasitizes the liver of mammal species, particularly rats and mice, although the list of host species is exceptionally long, including wild lagomorphs (Moreira et al, 2013). Cases of human infections with C. hepaticum have been reported in different continents and many of them have proved to be fatal (see Mowat et al, 2009).…”
Section: Discussionmentioning
confidence: 99%